PENGEMBANGAN PERANGKAT PEMBELAJARAN BIOLOGI BERBASIS INKUIRI TERBIMBING (PPBIT) DALAM MENINGKATKAN KEMAMPUAN BERARGUMEN SISWA - Dewi Seprianingsih; A Wahab Jufri; Jamaluddin - (Postgraduate, University of Mataram, 2017)
This study was aimed to develop inquiry-based learning tools (PPBIT) and analyzed its effectiveness in developing the ability to argue of students at SMAN 2 Taliwang-West Sumbawa. PPBIT was carried out by applying 4D procedure. Then, pretest posttest control group design also completely concerned in determining the effectiveness of PPBIT. There were 66 students as the sample which was scattered from two classes and was selected by using purposive sampling technique. The results showed that PPBIT was appropriately to be used for students argumentation skills’ activities by an average of feasibility syllabus 78.71%, RPP 83.5, LKITS 75%, and Instruments KB 80.25%, and effective in improving the ability to argue the class X SMAN 2 Taliwang, particularly on the subject of environmental pollution and recycling of waste by the average score of the students' ability from 48.22 up to 85.08.Keywords: PPBIT, Argument